The Impact Of Customer Relationship Management On Small And Medium Enterprises Performance - Mohamad, Siti Hajar; Othman, Norfaridatul Akmaliah; Jabar, Juhaini; Abdul Majid, Izaidin; Kamarudin, Mohd Fauzi (Penerbit UTeM, 2014)
-